Preconception health and care (PHC)—a strategy for improved maternal and child health. (1st October 2016) - Berglund, Anna; Lindmark, Gunilla
Abstract: Maternal health status before pregnancy is a decisive factor for pregnancy outcomes and for risk for maternal and infant complications. Still, maternity care does not start until the pregnancy is established and in most low-income settings not until more than half of the pregnancy has passed, which often is too late to impact outcomes. In Western societies preconception care (PCC) is widely recognized as a way to optimize women's health through biomedical and behavioural changes prior to conception with the aim of improving pregnancy outcomes. But the content of PCC is inconsistent and limited to single interventions or preconception counselling to women with chronic illnesses. It has been suggested that PCC should be extended to preconception health and care (PHC), including interventions prior to pregnancy in order to optimize women's health in general, and thereby subsequent pregnancy outcomes, the well-being of the family, and the health of the future child. With this definition, almost every activity that can improve the health of girls and women can be included in the concept. In the World Health Report of 2005 a longitudinal approach to women's wellness and reproductive health was highlighted, and the World Health Organization has proposed a more comprehensive maternal and child health care, also including psychosocial issues and intimate partner violence. The present article gives an overview of the recent literature and discusses contents and delivery of PCC/PHC in Western as well as low-income countries. The article puts special emphasis on why violence against women is an issue for PHC.